Online Pesantren: Architecture, Opportunities and Challenges - Zaki Mubarak (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2021)
Online pesantren is an alternative traditional Islamic institution in 21st century. It leads pesantren to open in virtual world becoming new entity of electronic educational ecosystem. Objective: this study aims to find online pesantren architecture without ignoring its character conceptually and practically. The process of knowledge transfer, value transfer and cultivating tradtion are tried to construct in internet of thing system. Society 5.0 as future concept of human life must be inserted by value of pesantren inside. Method: library research by grounded research was conducted by comparing and analyzing some primer books. Result: Online pesantren architecture consist of two main idea: internet architecture including modul and adopted pesantren virtual system and content architecture that consist of curriculum and material design, blended learning, and certification. The opportunity and challenge were found to strengthen online pesantren as a possibility although it conceptually needs deepest study to reconstruct definition, theory and practice of pesantren. Waiting society value artificial intelligent development will be a next solution to possible advance online pesantren.